Entering the fog of the gaze - Orloski, Christiane de Souza Coutinho; Orloski, Erick (Revista do Colóquio, 2025)
This essay presents and dissects the process of creation and development of a work of visual arts, entitled “Névoa” (2025), by Chris Coutinho. The text details each of the stages of construction of the work, covers conceptual and practical issues and establishes relations with different bibliographical references. The set of images, in turn, presents the assembly of the work in stages, superimposing each of the 8 (eight) layers that constitute the final work.